2019
DOI: 10.1002/acn3.50828
|View full text |Cite
|
Sign up to set email alerts
|

p75 and neural cell adhesion molecule 1 can identify pathologic Schwann cells in peripheral neuropathies

Abstract: Objective Myelinated Schwann cells (SCs) in adult peripheral nerves dedifferentiate into immature cells in demyelinating neuropathies and Wallerian degeneration. This plastic SC change is actively involved in the myelin destruction and clearance as demyelinating SCs (DSCs). In inherited demyelinating neuropathy, pathologically differentiated and dysmyelinated SCs constitute the main nerve pathology. Methods We investigated whether this SC plastic status in human neuropathic nerves could be determined by patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 35 publications
3
34
2
Order By: Relevance
“…Using the myelination and demyelination markers, MPZ and NCAM, respectively, we measured the myelination by Schwann cells at the sciatic nerve. Previously, it was reported that the expression level of NCMA correlated with demyelination status in the CMT1A mouse model [40]. Double staining with MPZ and NCAM antibodies revealed that control-diet-fed C22 mice had higher levels of NCAM and lower levels of MPZ compared to wild-type mice (Figure 5A).…”
Section: Farnesol Ameliorates Demyelinating Phenotype Of Cmt1a Mouse Modelmentioning
confidence: 67%
“…Using the myelination and demyelination markers, MPZ and NCAM, respectively, we measured the myelination by Schwann cells at the sciatic nerve. Previously, it was reported that the expression level of NCMA correlated with demyelination status in the CMT1A mouse model [40]. Double staining with MPZ and NCAM antibodies revealed that control-diet-fed C22 mice had higher levels of NCAM and lower levels of MPZ compared to wild-type mice (Figure 5A).…”
Section: Farnesol Ameliorates Demyelinating Phenotype Of Cmt1a Mouse Modelmentioning
confidence: 67%
“…Several biochemical features of DSCs in WD (wDSCs), such as the expression of c-jun and p75, together with shutdown of the expression of myelin genes and an increase in autolysosomes were also observed in the SC of the animal models of inflammatory demyelinating neuropathy, in which the axon is relatively intact [1,10,12]. Previous results and our recent study demonstrated the presence of potential DSCs in human inflammatory demyelinating nerves using biopsy specimens and patient sera, respectively [15,16], which suggests a pathological implication of DSCs in demyelinating neuropathies. However, the contribution of the demyelinating ability of DSCs, which may be inevitably accompanied by these inflammatory attack factors, on the pathogenesis of inflammatory demyelination has not been significantly considered in the clinical field.…”
Section: Introduction Of Demyelinating Schwann Cellsmentioning
confidence: 80%
“…Further blood biomarkers are currently investigated using proteomics approaches. Significant serum elevation of neural cell adhesion molecule-1 (NCAM1) was shown in CMT1A patients as well as in patients with various forms of inflammatory neuropathies [ 228 ]. This biomarker was also elevated in a mouse model of CMT1X and showed responsiveness to GJB1 gene replacement therapy [ 34 ].…”
Section: Clinical Trial Readiness For Cmt Neuropathiesmentioning
confidence: 99%